Cortical differences in diverticular disease and correlation with symptom reports - Pitiot, Alain; Smith, Janette Kate; Garratt, Jill; Francis, Susan T.; Gowland, Penny A.; Spiller, Robin C.; Marciani, Luca (Wiley, 2018)
Background